2022
DOI: 10.1155/2022/3992660
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Antiproliferative Activity in Different Plant Parts of Phaleria macrocarpa and the Underlying Mechanism of Action

Abstract: Phaleria macrocarpa is a medicinal plant widely used in Indonesian folk medicine to treat several diseases, including cancer. However, the comparative evaluation of various plant parts of P. macrocarpa has not been studied for their anticancer properties on breast cancer. The study aimed to assess the antiproliferative activity of the ethanol extract of various parts of Phaleria macrocarpa against T47D human breast cancer cell lines. Several parts of P. macrocarpa, including pericarp, mesocarp, seed, and leaf,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The leaves of each plant were washed, dried in an oven at 40°C, and ground to a fine powder. The fine powder was macerated in 95% ethanol (1:10) at room temperature (25°C) for 3 days, as described by Christina et al [9] and Christina et al [14]. The mixture was then filtered and evaporated in a rotary evaporator.…”
Section: Preparation Of Es and Sa Ethanol Extractsmentioning
confidence: 99%
“…The leaves of each plant were washed, dried in an oven at 40°C, and ground to a fine powder. The fine powder was macerated in 95% ethanol (1:10) at room temperature (25°C) for 3 days, as described by Christina et al [9] and Christina et al [14]. The mixture was then filtered and evaporated in a rotary evaporator.…”
Section: Preparation Of Es and Sa Ethanol Extractsmentioning
confidence: 99%
“…In a study by Chang et al, [10] anthraquinone rhein was purchased from Sigma-Aldrich, the IC50 values of rhein anthraquinone in T-47D/VEC and T-47D/HER2 cells were 36.69 ± 9.77 (129.1 µM) and 30.66 ± 2.21 µg/ml (107.9 µM) after 48 hours of treatment, respectively. However, the effects of this anthraquinone on other cancer cells were also good at different treatment times.…”
Section: Effect Of Rhein Anthraquinone On Cell Viabilitymentioning
confidence: 99%
“…This intensity indicates cells that have undergone apoptosis. Yuyunika et al [10] showed that Phaleria macrocarpa exhibited anti-proliferative and apoptotic effects on her T-47D cells. Apoptosis or programmed cell death mechanism is considered one of the proposed anti-tumor mechanisms of phenolic compounds [14].…”
Section: Effect Of Rhein Anthraquinone On Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The god's crown (Phaleria macrocarpa) is a plant often used by Indonesian human beings as a medicinal herb. This herb has compounds that effectiveness in cancer treatment [8][9][10] . Phaleria macrocarpa fruit holds alkaloids, saponins, and polyphenols 11 .…”
Section: Introductionmentioning
confidence: 99%